LOCAL GOVERNMENT IN THE PERSPECTIVE OF LAW NUMBER 23 OF 2014 - Oci, Yohanes; Dinanti, Ratu Yasmin Adara; Nabila, Bela (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Regional autonomy was born with consideration of the progress of economic development in the region and as a form of implementation of Article 18 of the 1945 Constitution which requires the formation of regional governments. Law No. 23 of 2014 concerning Regional Government as the legal umbrella for the implementation of regional government. In this law, several substances relate to the authority of regional heads, DPRD, and the relationship between these two institutions in administering government. The law also emphasizes the classification of regional government affairs. The classification of regional government affairs emphasizes that it is related to the obligations and direction of regional governments in running government. In this classification, there are government affairs. Absolute, concurrent government affairs, and general government affairs. Absolute government affairs cannot be given to regional governments, while concurrent government affairs are the underlying affairs in the implementation of regional government. This research is more about studying aspects of the implementation of Law No. 23 of 2014 with the urgency of regional development. The complexity of regional problems and the opportunities and challenges faced by each region are not the same, so the presence of regional governments that understand the roots of the problems that occur and the opportunities that exist becomes a study point in selected aspects of government affairs that refer to aspects of the opportunities and challenges that are currently or will be faced by the government area. With these considerations, the formulation in this research is related to the meaning of regional government and the perspective of the birth of Law No. 23 of 2014 in terms of the orientation of increasing or progressing regional development. Regions are the basis for national development because these problems must be addressed from the source where they occur, namely by using a bottom-up development pattern approach in addition to top-down in the policy-making process. The ability to understand the symptoms of government that are occurring and the ability to analyze policies must be used as a basis for regional development progress which will later be outlined in regional government policies or programs through the RPJPD, RPJMD, and RKPD. This research uses a literature review methodology, namely by examining various kinds of regulations that are the basis for the formation of regional governments, laws regarding regional government, and academic texts from Law No. 23 of 2014.